Obtaining Magnesium Compounds Based on the Processing of Rapa - Ruzieva, Z. T.; Soatova, P. B. (International Journal on Human-Computing Studies, 2023)
One of the main directions in economic development is the integrated use of local raw materials and the creation of production technology that can replace competitive imported products. The next important priority for the long-term perspective, which is of decisive importance in increasing the potential, power and competitiveness of our country, is active investment for the implementation of strategically important projects aimed at the modernization of the main leading industries, technical and technological renewal, development of transport and infrastructure communications. is to carry out the policy [1].